Cancer Immunology and Immunotherapy - Dranoff, Glenn; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The recent FDA approval of Provenge® as the first therapeutic cancer vaccine together with the recent demonstration that Ipilimumab®, a monoclonal antibody that blocks the negative immune checkpoint cytotoxic T lymphocyte associated antigen-4, prolongs patient survival are major achievements that usher in a new era of cancer immunotherapy. These “first-in-class” treatments reflect the substantive progress that basic and translational scientists have made towards understanding the mechanisms underlying protective tumor immunity in cancer patients Immunotherapies were first explored at the turn of the twentieth century, but the crafting of potent treatments required more detailed knowledge of how the immune system responds to cancer. Advances in genetic, cellular, and biochemical technologies have begun to yield this critical information, focusing attention on immune recognition, regulation, and escape. Indeed, the dynamic interplay of these processes in the tumor microenvironment is now recognized to play a decisive role in determining disease outcome. This volume highlights the rapid progress and breadth of research in cancer immunology, and provides a framework for anticipating many more clinical successes in cancer immunotherapy.
Keywords: Cancer research; Immunology; Cancer Research; Immunology